Engagement Across Generations: Navigating Employee Dynamics in Higher Education Post-COVID-19 - I Nyoman Sutapa; Magdalena Wullur; Isanti A. I.Edi; Soeharijadi (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Introduction: The study examines academic support staff engagement at a private university in Surabaya, Indonesia, from baby boomers to Gen Z. After COVID-19, managing multigenerational employees has been challenging. Older workers fear schedule and method changes. Online communication between academic support staff and lecturers is difficult. Different generations' ICT skills affect self-scheduling. The elderly have health and family responsibilities, while younger generations lack institutional commitment, causing exhaustion, monotony, and mental and physical health issues post-pandemic. We must address physical, social, and technological disparities and their effects on mental and physical health across generations. Objectives: This study seeks to investigate the impact of generational disparities on employee engagement amidst considerable changes in work practices and increased health concerns. Methods: An online survey of 375 employees yielded a 44.8% response. Based on Maslach and Leiter's Vigor, Dedication, and Absorption, the survey used a Likert scale. A structured methodology, consent, and Google Forms data collection ensured anonymity and confidentiality in the study. The study's goals and significance were also explained. One-way ANOVA was used to compare generational engagement and Cronbach's alpha for reliability. Results: Gen Z engages least and Baby Boomers most. These differences show age cohorts' work motivations and expectations. Baby Boomers are more resilient and dedicated than Gen Z, requiring customized engagement. Low participation in Generation X and Millennials suggests different workplace preferences, job satisfaction, and work-life balance. Conclusions: The findings show how life, technology, and workplace expectations affect generational work styles. Many boomers work hard and loyally. Resilience, role dedication, and institutional duty motivate them. Early workforce entry, inexperience, and hybrid work paradigm issues may explain Generation Z's low engagement. Lower Gen Z employee engagement suggests they need more inclusive and supportive engagement strategies like work flexibility, technological integration, and fast, professional advancement. For Generation X and Millennials, moderate engagement suggests work-life balance and meaning.